2014
DOI: 10.1177/0040517513515316
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic shielding effectiveness of polyester fabrics with polyaniline deposition

Abstract: In this study, conductive fabrics were developed by polymerizing aniline onto polyester (PET) woven fabrics. The fabric treatment was carried out by the chemical polymerization method at 0.5 M, 0.8 M and 1.2 M aniline concentrations. Hydrochloric acid as acidic medium and ammonium persulfate as oxidant were employed during the polymerization process. The polyaniline (PANI)-treated PET fabric structures were fully characterized and evaluated in terms of their electromagnetic shielding effectiveness, absorption … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 36 publications
(48 reference statements)
1
36
0
Order By: Relevance
“…This ratio coincides very well with the findings of Stejskal et al [3,44], who proposed the oxidant/monomer molar ratio of 1.25 as a proper compromise between the changes in conductivity of PANI pellets and the yield of conductive polymer. Engin and Usta [5] investigated several oxidant/aniline molar ratios and observed that the combination of 1:1 ratio with 0.8 M ammonium persulfate showed the highest mechanical properties and conductivity, as well as a decrease in conductivity at 1.2 M aniline on PET fabric. Fig.…”
Section: Pani Prints On Textile Substratesmentioning
confidence: 99%
See 1 more Smart Citation
“…This ratio coincides very well with the findings of Stejskal et al [3,44], who proposed the oxidant/monomer molar ratio of 1.25 as a proper compromise between the changes in conductivity of PANI pellets and the yield of conductive polymer. Engin and Usta [5] investigated several oxidant/aniline molar ratios and observed that the combination of 1:1 ratio with 0.8 M ammonium persulfate showed the highest mechanical properties and conductivity, as well as a decrease in conductivity at 1.2 M aniline on PET fabric. Fig.…”
Section: Pani Prints On Textile Substratesmentioning
confidence: 99%
“…An interesting alternative is to create the conductive polymers by in-situ polymerization of monomers on the textiles. Basically, the oxidative polymerization on a fabric may follow three procedures: application of the oxidant to the textile followed by addition of monomer, application of monomer followed by oxidizing agent, and application of a polymerizable mixture of monomer and oxidant [4,5]. Among the different methods of PANI deposition, the ink-jet printing technique is very attractive as it allows not only patterns of high resolution and high repeatability to be obtained, but also repeatable layer-by-layer structures.…”
Section: Introductionmentioning
confidence: 99%
“…Conducting polymers, such as polyaniline and polypyrrole, well serve for this purpose [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Conducting textiles find applications as antistatic substrates [3], in electromagnetic interference shielding [6,[9][10][11][12][13][14][15], electrochromic devices [16], electromechanical sensors [17,18], electrodes in supercapacitors [4,19], electrocardiogram monitoring [20] or dye-sensitized solar cells [21], as flexible electrodes [22], or in heat generation [23][24][25]. In addition to conductivity, conducting polymers have been be used to control wettability [5,26,27], to promote flame retardation [28][29][30], to be applied as antimicrobial coatings [15,31,32] or in noble-metal recovery [33].…”
Section: Introductionmentioning
confidence: 99%
“…The novel functionalities and properties can be introduced by modifying the textile materials or integrating the electronic devices into the textile structures [1]. Generally, the demand for the electrically conductive fibers and textiles is rapidly growing in relation to industrial needs such as sensing, electrostatic discharge, corrosion protection, electromagnetic interference shielding, dust-and germ-free clothing, monitoring and data transfer in clothing [1][2][3].…”
Section: Introductionmentioning
confidence: 99%